Automated Semantic Annotation of Data Management Plans: A Systematic Review - Jana Martínková; Marek Suchánek; Petr Kroha (Data Science Journal)
Semantic annotation has emerged as a key technique for transforming human-readable data into machine-actionable formats. It corresponds with the growing emphasis on data reusability and research reproducibility. This paper examines tools for semantic annotation using ontologies and controlled vocabularies, with a focus on their application in data management planning. A systematic review identified 34 relevant tools, which show potential for adaptation to the data management plan (DMP) domain. While these tools meet many requirements, they do not fully address all DMP-specific needs. The paper provides an overview of current tools and suggests directions for future research to adapt them for DMP use.